1988
DOI: 10.1073/pnas.85.15.5414
|View full text |Cite
|
Sign up to set email alerts
|

Herpes simplex virus DNA replication: the UL9 gene encodes an origin-binding protein.

Abstract: Herpes simplex virus 1 contains seven genes that are necessary and sufficient for origin-dependent DNA synthesis in cultured cells. We have expressed the product of one of these genes, UL9, in insect cells by using a baculovirus expression vector. The apparent size of the UL9 protein, both in insect cells and in herpes simplex virus-infected Vero cells, is 82,000 Da. By using an immunoassay for protein-DNA interaction, we have shown that UL9 protein binds specifically to the herpes simplex virus origins of DNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
142
0

Year Published

1989
1989
2001
2001

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(145 citation statements)
references
References 21 publications
3
142
0
Order By: Relevance
“…Heteropolymeric DNA is much less effective than homopolymeric DNA in stimulating the DNA-dependent ATPase activity of the HSV-1 origin-binding protein, which is also a DNA helicase and is encoded by the UL9 gene (21)(22)(23). Both poly(dT) and poly(dC) effectively activated the ATPase activity of the UL5/UL52 subassembly (Fig.…”
Section: Fig 1 Effect Of Ph Mgmentioning
confidence: 99%
“…Heteropolymeric DNA is much less effective than homopolymeric DNA in stimulating the DNA-dependent ATPase activity of the HSV-1 origin-binding protein, which is also a DNA helicase and is encoded by the UL9 gene (21)(22)(23). Both poly(dT) and poly(dC) effectively activated the ATPase activity of the UL5/UL52 subassembly (Fig.…”
Section: Fig 1 Effect Of Ph Mgmentioning
confidence: 99%
“…DNase footprinting and gel retardation studies demonstrated that the UL9 protein binds to two sites within ori s which overlap the ends of the palindromic DNA sequence ( Fig. 1) (Elias & Lehman, 1988;Koff & Tegtmeyer, 1988;Olivo et al, 1988;Weir et al, 1989). The results of methylation interference and site-directed mutagenesis experiments indicate that the UL9 recognition sequence comprises, or is included within, YGYTCGCACT (where Y represents C or T) (Koff & Tegtmeyer, 1988;Deb & Deb, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…One of these proteins, encoded by the UL9 gene, binds to specific sequences within the origin regions (Olivo et al, 1988;Weir et al, 1989). DNase footprinting and gel retardation studies demonstrated that the UL9 protein binds to two sites within ori s which overlap the ends of the palindromic DNA sequence ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Firstly, UL9 is a sequence-specific DNAbinding protein which interacts with defined sites within the viral origins of replication. These sequences are recognized in double-stranded DNA with the C-terminal 317 amino acids being sufficient for binding (Olivo et al, 1988;Koff & Tegtmeyer, 1988;Weir et al, 1989). Secondly, UL9 exhibits DNA helicase and associated DNA-dependent ATPase activities (Fierer & Challberg, 1992;, consistent with the presence of several motifs characteristic of a superfamily of DNA and RNA helicases within the N-terminal 400 amino acids (Gorbalenya & Koonin, 1993).…”
mentioning
confidence: 99%